A Clinical Trial to Detect Subclinical Transfusion-induced Lung Injury during Surgery. (July 2015) - Feiner, John R.; Gropper, Michael A.; Toy, Pearl; Lieberman, Jeremy; Twiford, Jenifer; Weiskopf, Richard B.
Abstract : Background: Transfusion-related acute lung injury incidence remains the leading cause of posttransfusion mortality. The etiology may be related to leukocyte antibodies or biologically active compounds in transfused plasma, injuring susceptible recipient's lungs. The authors have hypothesized that transfusion could have less severe effects that are not always appreciated clinically and have shown subtly decreased pulmonary oxygen gas transfer in healthy volunteers after transfusion of fresh and 21-day stored erythrocytes. In this study, the authors tested the same hypothesis in surgical patients. Methods: Ninety-one patients undergoing elective major spine surgery with anticipated need for erythrocyte transfusion were randomly allocated to receive their first transfusion of erythrocytes as cell salvage (CS), washed stored, or unwashed stored. Clinicians were not blinded to group assignment. Pulmonary gas transfer and mechanics were measured 5 min before and 30 min after erythrocyte transfusion. Results: The primary outcome variable, gas transfer, as assessed by change of PaO2 /FIO2, with erythrocyte transfusion was not significant in any group (mean ± SD; CS: 9 ± 59; washed: 10 ± 26; and unwashed: 15 ± 1) and did not differ among groups ( P = 0.92). Pulmonary dead space (VD/VT) decreased with CS transfusion (−0.01 ± 0.04; P = 0.034) but did not change with other erythrocytes; the change from before to after erythrocyte transfusion did not differ among groups (−0.01 to +0.01; P = 0.28). Conclusions: The authors did not find impaired gas exchange as assessed by PaO2 /FIO2 with transfused erythrocytes that did or did not contain nonautologous plasma. This clinical trial did not support the hypothesis of erythrocyte transfusion-induced gas exchange deficit that had been found in healthy volunteers. Abstract : In this study, transfused erythrocytes in surgical patients did not impair gas exchange as assessed by PaO2 /FIO2 .Supplemental Digital Content is available in the text.